Improving Job Satisfaction and Work Environment in Boosting Employee Performance at Pt. Savana Rattan Furniture - Siti Chaerunisah; Noveria Susijawati (Rescollacom (Research Collaborations Community), 2026)
Employee performance is a critical factor influencing organizational productivity, particularly in labor-intensive manufacturing industries such as the rattan furniture sector. This study aims to examine the effect of job satisfaction and work environment on employee performance at PT Savana Rattan Furniture Indonesia. A quantitative approach was employed using a survey method with questionnaires distributed to 110 employees selected through proportionate stratified random sampling. Data analysis was conducted using SPSS, including validity and reliability testing, descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results indicate that job satisfaction has a positive and significant effect on employee performance. Employees with higher levels of job satisfaction tend to demonstrate better productivity, work consistency, and performance outcomes. Similarly, the work environment was found to have a positive and significant effect on employee performance. A conducive work environment contributes to improved employee comfort, focus, and work effectiveness. Furthermore, job satisfaction and work environment simultaneously influence employee performance, with the regression model demonstrating strong explanatory power. These findings highlight the importance of psychological and organizational factors in enhancing employee performance. Improving employee satisfaction and creating a supportive work environment are essential strategies for maintaining productivity and performance stability, particularly in manual skills-based industries. This study provides empirical insights for organizations seeking to optimize workforce performance through human resource management practices.